(untitled) (ModaPalavra e-periódico, 2021)
In this article, the symbolic values and discursive strategies present in fashion editorials produced by two different models of clothing companies are analyzed: one fast fashion brand and one slow fashion brand. To this end, the theoretical-methodological apparatus of discursive semiotics developed by Algirdas Julien Greimas is used, with a view to raising interpretive hypotheses and apprehending the effects of meaning linked to the photographic images of these two business models. As a result, the readings of the visual elements that are part of the analyzed editorials suggest the promotion of distinct values that point to the possible ideological positions discursivized by the brands.